GENETIC FEATURES AND RESOURCES OF RARE METAL DEPOSITS OF THE UKRAINIAN SHIELD - Zagnitko, V.; Mykhailov, V.; Kryvdic, S.; Sydorchuk, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Rare metals are an important part of the global economy. Ukraine has developed mineral raw material base of rare metals, but no one of its objects is currently being developed now, causing damage to the national economy of Ukraine. Almost all known endogenous rare metal deposits of the Ukrainian Shield (Zr, Nb, Ta, TR, Sr, Li, Be, Rb, etc.) are related genetically to Paleoproterozoic complexes (1,7–2,1 Ga) of alkaline rocks, carbonatites and pegmatites. The majority of these deposits belong to well-known traditional types, but they have a number of specific and even unique mineralogical, geochemical and petrological features. In addition, the new deposit types were found in this region, not reported in the other Precambrian shields (including nepheline-free syenites highly enriched in Zr and TR, petalite pegmatites, U-Sc-V metasomatites, genthelvite deposits of Be and others). The objective of this article was to show the features and potential of rare-metal mineralization in the Ukrainian shield, to evaluate the resources of rare metals using so-called uniqueness ratio, calculated as the ratio of inferred resources of chemical elements to their clarkes in earth's crust. There are the following types of deposits at the Ukrainian shield for niobium resources: giant one is Chernigivske (Novopoltavske), the large ones are Oktyabrske and Yastrubetske; for zirconium: giant one is Yastrubetske, medium ones are Chernigivske, Oktyabrske and Azovske; for rare earth elements: large ones are Chernigivske and Yastrubetske, medium ones are Oktyabrske and Azovske; for tantalum: large ones are Chernigivske and Oktyabrske; for strontium: large one is Chernigivske; for lithium: medium one is Polokhivske deposit in petalite pegmatites; for scandium: large one is Zhovtorichenske. This estimation will contribute to objective evaluation of investment attractiveness level of these deposits. Moreover, most of the ore objects are of a complex type, so even medium and small size deposits can show high level of investment attractiveness, considering a well-developed infrastructure and presence of mining and processing plants on the territory of the Ukrainian shield.
Keywords: rare metals; deposits; resources; uniqueness ratio